FUNGSI TINDAK UJAR KONFLIKTIF DALAM FILM THE CHRONICLES OF NARNIA THE LION, THE WITCH AND THE WARDROBE KARYA C.S. LEWIS SUATU ANALISIS PRAGMATIK - MENTANG, LINDA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT Â Language is one of the characteristics of human beings that differentiate them from other creatures. In this case, human beings use language as a tool of communication. In uttering something, people are not only sounding sentence, but also transferring it into behavior. This is called speech acts, and illocutionary act is one of the aspects of it. This study focuses on one of the categories of illocutionary act, conflictive act that is used in the film The Chronicles of Narnia, the Lion, the Witch and the Wardrobe by C.S. Lewis. In collecting the data, the writer elicits the data through the conversation among the characters in the film. To analyze the data the writer uses Leechâ€™s theory. Leech divided conflictive act into four kinds which is are threatening, reprimanding, accusing and cursing. It is hoped that one kind of conflictive act that is not found in this research which is cursing, can be found in other research. However, it is suggested for researchers to use another theory of illocutionary acts in other objects such as native language, novel, short story and many others. Â Keywords: Speech act; Illocutionary act; Conflictive act; Film : The Chronicles of Narnia, the Lion, the Witch and the Wardrobe.